Selective synthesis of mono- and distannylpyridines from chloropyridinols via an SRN1 mechanism - Silbestri, Gustavo Fabián (2010)
A selective two-step synthesis of either mono- or distannylated pyridines from commercially available pyridinols, involving its conversion to the corresponding diethyl pyridyl phosphates (pyDEP) followed by the reaction with Me3SnNa in liquid ammonia, is described. The results obtained clearly indicate that the reactions proceed through an unimolecular radical nucleophilic substitution mechanism (SRN1) with intermediacy of a monosubstitution product.